The construction of the tourist gaze in English textbooks in South Korea: exploring the tensions between internationalisation and nationalisation. Issue 2 (4th May 2019) - Vinall, Kimberly; Shin, Jaran
ABSTRACT: This study investigates how larger ideological tensions related to internationalisation and nationalisation are manifested in local education systems, especially in English textbooks. We begin this exploration with a review of the School Curriculum of the Republic of Korea. Using three textbooks as cases; we examine how they reflect and manage the tensions presented in the Curriculum. We argue that these tensions are managed through the construction of a tourist gaze, which is both directed inwards, in the construction of Koreanness, and outwards, in the construction of a global citizen. Through the medium of English, learners are both tourists, viewing their own culture from the perspective of the 'other, ' while they are being prepared to be 'tour guides, ' learning how to explain this perspective to the 'other' in the other's language, English. When focused outwards, the tourist gaze constructs representations of foreign cultures because it is through learning English that Korean learners become global citizens and are able to connect to 'others, ' to make friends, and to travel the world. We conclude with considerations of ways to go beyond the tourist gaze, as teachers and learners use the tensions in more constructive ways – namely, to develop critical cultural competence.